Are the Derived Indexes of Peripheral Whole Blood Cell Counts (NLR, PLR, LMR/MLR) Clinically Significant Prognostic Biomarkers in Multiple Myeloma? A Systematic Review And Meta-Analysis - Zhang, Xinwen; Duan, Jialin; Wen, Zhenyu; Xiong, Hao; Chen, Xiaomin; Liu, Yang; Liao, Kunyu; Huang, Chunlan (Frontiers in Oncology, 2021)
Abstract Background: Multiple myeloma (MM) is an incurable malignant plasma cell tumor. Whole blood cell count (WBCC) derived indexes are widely used as a predictive biomarker for various types of solid and hematological malignant tumors. Our study is to evaluate its effectiveness in MM by meta-analysis. Methods: Relevant literatures were retrieved from PubMed, Embase and Web of Science databases according to PRISMA guideline. All relevant parameters were extracted and combined for statistical analysis. Results: Nineteen studies incorporating 3818 MM patients were eventually included in this meta-analysis. 13 studies evaluated that elevated NLR was significantly associated with poor survival outcomes (OS: HR=2.04, P<0.001; PFS: HR=1.96, P=0.003). Elevated NLR was revealed to correlate with ISS stage (ISS III VS I-II, OR=2.23, P=0.003). A total of 7 studies have shown that elevated LMR predicts a better prognosis in MM patients (OS: HR=0.57, P<0.001; PFS: HR=0.49, P<0.05), and two other studies demonstrated that increased MLR was related to poor OS/PFS (OS: HR=1.58, P<0.05; PFS: HR=1.60, P<0.05). However, in the other 6 studies including 1560 patients, the prognostic value of PLR had not been confirmed (OS: HR=0.89, P>0.05; PFS: HR=0.87, P>0.05). Conclusions: The indexes NLR and LMR/MLR derived from WBCC were validated to be useful biomarkers to predict the prognosis in MM patients, but the evidence of PLR was insufficient.